Heat treatment of silanized feldspathic ceramic: Effect on the bond strength to resin after thermocycling - De Figueiredo, Viviane Maria Gonçalves [UNESP] (2015)
Purpose This study aimed to evaluate the effect of heat treatment (at 77 °C) of a silanized feldspathic ceramic on microtensile bond strength (μTBS) with a resin cement before and after being aged by thermocycling. Material and methods Twenty-four blocks (12×10×4 mm3) of a CAD/CAM feldspathic ceramic (Vitablocks Mark II, Vita) were obtained and randomly divided into three groups, according to the surface treatment prior to the cementation: Group AS - hydrofluoric acid 10%+silane; Group S77 - silane+heating at 77 °C for 60 s; and Group AS77 - hydrofluoric acid 10%+silane+heating at 77 °C for 60 s. Ceramic blocks were cemented to composite resin blocks with a resin cement. The sets were subsequently cross-sectioned into 1 mm2 beams for μTBS testing. The beams of each group were randomly divided into two subgroups: aging (thermocycling, 12,000 cycles between 5 °C and 55 °C) and non-aging (tested immediately). One-way ANOVA and Tukey's test (α=0.05) and Weibull analysis (95% CI) were used to analyze the data. Results Group AS77 had the lowest pre-test failure number during the cutting among the groups. There was no significant difference (p=0.255) between the μTBS mean values of the non-aged groups. After aging, the mean value of S77 was significantly lower than those of AS77 and AS (p=0.005). There was no difference in the Weibull modulus (m) and characteristic strength (σ0) of the aged and non-aged groups for all comparisons. Before aging, heat treatment of silanized feldspathic ceramic (non acid-etched surface) demonstrated bond strength similar to that achieved with hydrofluoric-acid-etching treatment however, it had lower bond strength after aging. Conclusion The combination of hydrofluoric-acid-etching treatment with heat treatment silanized feldspathic ceramic did not improve the bond strength of the interface.